Accuracy of faecal calprotectin and neutrophil Gelatinase B-associated Lipocalin in evaluating subclinical inflammation in UlceRaTIVE colitis-the ACERTIVE study - Magro, Fernando (2017)
Background and Aims: Mucosal healing and histological remission are different targets for patients with ulcerative colitis, but both rely on an invasive endoscopic procedure. This study aimed to assess faecal calprotectin and neutrophil gelatinase B-associated lipocalin as biomarkers for disease activity in asymptomatic ulcerative colitis patients. Methods: This was a multicentric cross-sectional study including 371 patients, who were classified according to their endoscopic and histological scores. These results were evaluated alongside the faecal levels of both biomarkers. Results: Macroscopic lesions [i.e. endoscopic Mayo score >= 1] were present in 28% of the patients, and 9% had active disease according to fht Ulcerative Colitis Endoscopic Index of Severity. Moreover, 21% presented with histological inflammation according to the Geboes index, whereas 15% and 5% presented with focal and diffuse basal plasmacytosis, respectively. The faecal levels of calprotectin and neutrophil gelatinase B-associated lipocalin were statistically higher for patients with endoscopic lesions and histological activity. A receiver operating characteristic-based analysis revealed that both biomarkers were able to indicate mucosal healing and histological remission with an acceptable probability, and cut-off levels of 150-250 mu g/g for faecal calprotectin and 12 mu g/g for neutrophil gelatinase B-associated lipocalin were proposed. Conclusions: Faecal calprotectin and neutrophil gelatinase B-associated lipocalin levels are a valuable addition for assessment of disease activity in asymptomatic ulcerative colitis patients. Biological levels of the analysed biomarkers below the proposed thresholds can rule out the presence of macroscopic and microscopic lesions with a probability of 75-93%. However, caution should be applied whenever interpreting positive results, as these biomarkers present consistently low positive predictive values.